Resources, experience, and perseverance in entrepreneurs' perceived likelihood of success in an emerging economy - Quan Hoang Vuong; Thu Hang Do; Thu Trang Vuong Thu Hang Do (Journal of Innovation and Entrepreneurship, 2016)
This paper introduces new results obtained from a statistical investigation into a 3071-observation data set collected from a Vietnamese nationwide entrepreneurship survey. From established relationships, such factors as preparedness, financial resources, and participation in social networks are confirmed to have significant effects on entrepreneurial decisions. Entrepreneurs, both financially constrained and unconstrained, who have a business plan tend to start their entrepreneurial ventures earlier. Also, financial constraints have a profound impact on the entrepreneurial decisions. When perceiving the likelihood of success to be high, an entrepreneur shows the tendency for prompt action on business ideas. But when seeing the risk of prolonging the waiting time to first revenue, a prospective entrepreneur would be more likely to wait for more favorable conditions despite the vagueness of "favorable." Additionally, empirical computations indicate that there is a 41.3 % probability that an extant entrepreneur who is generating revenue sees high chance of success. Past work and entrepreneurial experiences also have positive impacts on both the entrepreneurial decisions and perceived chance of success.
Keywords: L26; M13; P27; 650; Entrepreneurship; New venture; Transitional economies